2018
DOI: 10.1103/physrevb.97.075103
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen holes and hybridization in the bismuthates

Abstract: Motivated by the recently renewed interest in the superconducting bismuth perovskites, we investigate the electronic structure of the parent compounds ABiO3 (A = Sr, Ba) using ab initio methods and tight-binding (TB) modeling. We use the density functional theory (DFT) in the local density approximation (LDA) to understand the role of various interactions in shaping the ABiO3 bandstructure near the Fermi level. It is established that interatomic hybridization involving Bi6s and O-2p orbitals plays the most imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
98
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(110 citation statements)
references
References 40 publications
11
98
1
Order By: Relevance
“…As shown in Fig. 5 and 6, for BaBiO 3 , CaFeO 3 and SmNiO 3 , the ligand contribution to the CBM is much larger than that from the B atom, consistent with the previous observation/prediction 17,29,43 , while for CsTlF 3 and CsAuCl 3 , the CBM has almost a similar contribution from the ligand and the B atom. We will further discuss such ligand hole states in Sec.…”
Section: Energy Lowering Upon Dle Formation Is Accompanied By Gapisupporting
confidence: 89%
See 2 more Smart Citations
“…As shown in Fig. 5 and 6, for BaBiO 3 , CaFeO 3 and SmNiO 3 , the ligand contribution to the CBM is much larger than that from the B atom, consistent with the previous observation/prediction 17,29,43 , while for CsTlF 3 and CsAuCl 3 , the CBM has almost a similar contribution from the ligand and the B atom. We will further discuss such ligand hole states in Sec.…”
Section: Energy Lowering Upon Dle Formation Is Accompanied By Gapisupporting
confidence: 89%
“…We phrase below a number of questions posed regarding disproportionation in ABX 3 compounds, and will address them in this paper by considering six compounds showing DLE behavior, including BaBiO 3 , 9,10,[16][17][18][19][20] (a) What level of electronic structure theory is sufficient to predict the energetic tendency ( Fig. 1…”
Section: The Main Questions Addressed With Respect To Sle Vs Dle mentioning
confidence: 99%
See 1 more Smart Citation
“…Doped BaBiO3 (BBO) superconductors possess a commensurate CDW in the parent compound, stable to high temperatures, in an isotropic, nonmagnetic complex oxide. The CDW manifests as bond disproportionation through a frozen breathing mode of the BiO6 octahedra, as pictured in Figure 1(a), with recent experimental and first principle work suggesting hybridization of the BiO6 octahedra plays a dominate role [3][4][5][6]. Doping BBO with Pb in BaPb1-xBiXO3 (BPBO, Tc=11 K) or K in Ba1-xKxBiO3 (BKBO, Tc=30 K) destroys the long range CDW [7][8][9].…”
mentioning
confidence: 87%
“…To hybridize with Bi 6s orbitals, only O 2p δ orbitals with A 1g symmetry are allowed. For low energy electronic excitations in BaBiO 3 , Khazraie et al estimated effective hopping integrals for nearest neighbor and next nearest neighbor using a single orbital tight binding model [26]. They showed that with the breathing distortion of A 0.1  and no external electric field, the size of the hopping integral t 1 between nearest neighbors involving oxygen atoms with A 1g symmetry is four times larger than that of the next nearest neighbor hopping integral t 2 between two Bi ions sit at a distance a 2 as shown in figure 6(e).…”
Section: Dielectric Constant Measurementsmentioning
confidence: 99%